Clinicopathological Implication of Long Non-Coding RNAs SOX2 Overlapping Transcript and Its Potential Target Gene Network in Various Cancers - Li, Yishu; Du, Mengyu; Wang, Shengsheng; Zha, Jin; Lei, Peijie; Wang, Xueqi; Wu, Di; Zhang, Jianhua; Chen, Denggang; Huang, Dong; Lu, Jing; Li, Heng; et al. (Frontiers in Genetics, 2020)
Background: SOX2 overlapping transcript (SOX2-OT) produced alternatively spliced long non-coding RNAs (lncRNA). The prognostic role of SOX2-OT expression had been explored in various researches, however, with conflicting results. The aim of this study was to properly consider the prognostic role of SOX2-OT expression in several cancers. Besides, the regulative mechanism of SOX2-OT is still equivocal. Methods: PubMed, EMBASE, and Cochrane Library and The Cancer Genome Atlas (TCGA) database were comprehensively explored to recover pertinent studies. We conducted an extensive inquiry to verify the implication of SOX2-OT expression in cancer patients by conducting a meta-analysis of 13 selected studies. 32 TCGA databases were used to analyze the connection between SOX2-OT expression and both the overall survival (OS) and clinicopathological characteristics of cancer patients using R and STATA 13.0. Trial sequential analysis (TSA) was adopted in order to compute the studies’ power. Results: 13 studies involving 1172 cancer patients and 32 TCGA cancers involving 9676 cancer patients were eventually selected. Elevated SOX2-OT expression was significantly related to shorter OS in cancers (HR = 2.026, 95% CI: 1.691-2.428, P < 0.0001) and disease free survival (DFS) (HR = 2.554, 95% CI: 1.261-5.174, P = 0.0092). Meanwhile, TSA substantiated adequate power to demonstrate the relationship of SOX2-OT expression and OS. The cancer patients with elevated SOX2-OT expression were more likely to have advanced clinical stage (RR = 1.468, 95% CI: 1.106-1.949, P = 0.0079), earlier lymphatic metastasis (P = 0.0005), earlier distant metastasis (P < 0.0001), greater tumor size (P < 0.0001), and extremer tumor invasion (P < 0.0001) compared to those with low SOX2-OT expression. Meta-regression and subgroup analysis revealed that follow up time, sample type, and tumor type could significantly contribute to heterogeneity for survival outcomes. The follow up time could significantly explain heterogeneity for TNM stage. Conclusions: Elevated expression of SOX2-OT predicted a poor OS and DFS. Overexpression of SOX2-OT was correlated with more advanced tumor stage, earlier lymphatic metastasis, earlier distant metastasis, larger tumor size, and deeper tumor invasion. SOX2-OT-mediated cell adhesion or mRNA binding or mRNA surveillance could be an intrinsic mechanism for invasion and metastasis.